PROTECTIVE STRATEGIES FOR CHRONIC KIDNEY DISEASE (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Chronic kidney disease (CKD) is a growing global health concern with significant socioeconomic implications. Effective prevention strategies are crucial to mitigate its progression and associated complications. This article highlights evidence-based preventive approaches, including lifestyle modifications, early detection through screening, pharmacological interventions, and public health initiatives. It also emphasizes the importance of policy support and healthcare provider engagement in CKD prevention.